ANALYSIS OF FACTORS INHIBITING IMPLEMENTATION INDEPENDENT CURRICULUM AT STATE JUNIOR HIGH SCHOOL 1 AFULU NORTH NIAS REGENCY - Samania Waruwu; Syah Abadi Mendrofa; Odaligoziduhu Halawa; Nany Artatina Buulolo (Jurnal Ilmiah METADATA, 2026)
This study aims to analyze the implementation and identify factors inhibiting the implementation of the Independent Curriculum at SMP Negeri 1 Afulu, North Nias Regency. The study used a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Research informants consisted of the principal and teachers directly involved in curriculum implementation. Data analysis was conducted using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The results show that the implementation of the Independent Curriculum has been ongoing at the planning and implementation stages of learning, including the development of teaching modules and the implementation of the Pancasila Student Profile Strengthening Project (P5). However, its implementation has not been optimal. The main inhibiting factors include a lack of teacher training, limited facilities and infrastructure, a conventional learning system, limited internet access, and a lack of supporting facilities for project-based learning. These findings indicate that the successful implementation of the Independent Curriculum is highly dependent on the readiness of human resources, school managerial support, and the availability of adequate educational infrastructure.